AVALIAÇÃO DA ATIVIDADE PROLIFERATIVA DA MUCOSA ORAL DE USUÁRIOS DO CRACK - BOHN, Joslei Carlos; CHAIBEN, Cassiano Lima; MACHADO, Maria Ângela Naval; TOMMASI, Maria Helena Martins; de LIMA, Antonio Adilson Soares (DENS, 2011)